Preparation method of macroporous hollow water treatment material
A macroporous hollow water treatment material was prepared by coating polyethylene microspheres with a samarium titanate-copper oxide composite coating. This method solved the problem of catalyst-water separation, improved wastewater treatment efficiency and material recycling, and is suitable for the purification of various organic wastewaters.
Patent Information
- Application Number
- CN202410934627.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Existing photocatalytic technologies face challenges in separating the catalyst from water during wastewater treatment, affecting treatment efficiency and recycling. Furthermore, traditional biochemical treatments are ineffective in removing toxic and harmful substances.
A method for preparing macroporous hollow water treatment materials was adopted. By coating polyethylene microspheres with a samarium titanate-copper oxide composite active coating, a material with moderate density was formed, which is easy to suspend and separate. Combined with solvothermal synthesis and heat treatment processes, a highly active photocatalytic material was prepared.
It enables convenient separation of catalyst and water, facilitates recycling, improves the purification efficiency of organic pollutants in wastewater, and is suitable for the treatment of various types of wastewater.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental pollution purification materials, specifically relating to a method for preparing a macroporous hollow water treatment material. Background Technology
[0002] Industrial and domestic wastewater contains a wide variety of pollutants, including various toxic and harmful organic compounds. Traditional biochemical treatment techniques can be used to treat organic pollutants in wastewater, but the toxicity of these substances on the microorganisms essential for the process often results in unsatisfactory treatment efficiency.
[0003] Photocatalytic oxidation is a deep oxidation technology capable of degrading the vast majority of organic pollutants in water. After half a century of in-depth research, photocatalysis is playing an increasingly important role in the purification of toxic and harmful organic pollutants. The key to photocatalytic treatment is ensuring thorough mixing of the catalyst with the organic pollutants in the wastewater, allowing these organics to decompose under light to achieve purification. In continuous, large-scale wastewater treatment processes, the separation of the photocatalyst from the water is a crucial factor. Photocatalytic materials must not only possess high treatment activity but also be easily separated from water after treatment for recycling. Summary of the Invention
[0004] To address the problems existing in the prior art, this invention aims to provide a method for preparing a macroporous hollow water treatment material that can be used in the photocatalytic purification process of organic pollutants in wastewater.
[0005] The technical solution adopted in this invention is:
[0006] A method for preparing a macroporous hollow water treatment material includes the following process steps:
[0007] Step 1: Preparation of sol precursor
[0008] (1) Add 160-180 mL of anhydrous ethanol, 7.5-9 mL of 1,3-butanediol, 5.5-6.5 g of samarium nitrate, and 8.0-9.5 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed;
[0009] (2) Add 2.3-2.7g Tween 80, 3.1-3.6g copper chloride, and 1.2-1.3mL acetic acid to 35-45mL of pure water, and stir until solution B is formed;
[0010] (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor;
[0011] Step 2: Polyethylene microbead gelation and coating
[0012] (1) Add 20g of polyethylene microbeads to the flask containing the sol precursor and continue to reflux at 65℃ for 50min to obtain suspension A;
[0013] (2) Concentrate suspension A by rotary evaporation at 85°C until the volume of suspension A is reduced by 30% to obtain suspension B;
[0014] Step 3: Solvothermal Synthesis
[0015] (1) Transfer suspension B into a stainless steel high-pressure reactor, control the temperature of the solution in the reactor to 155-165℃, the pressure in the reactor to less than 2.2MPa, react for 60h, and then cool to room temperature to obtain suspension C;
[0016] (2) Filter the suspension C, and dry the solid obtained by filtration at 150°C for 18 hours to obtain solid A;
[0017] Step 4: Heat treatment
[0018] (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours.
[0019] (2) Continue to raise the temperature to 670-750℃ at a heating rate of 10℃ / min, calcine for 5h, and obtain the calcined product;
[0020] (3) Cool the calcined product to room temperature and grind it into a loose powder to obtain a macroporous hollow water treatment material.
[0021] Furthermore, the polyethylene microspheres described in step (2) have a particle diameter of 0.7 to 0.8 mm and a density of 1.0 g / mL.
[0022] A macroporous hollow water treatment material is prepared by the above method, wherein the macroporous hollow water treatment material is coated with a samarium titanate-copper oxide composite active coating on polyethylene microspheres, so that the coating is firmly bonded to the polyethylene microspheres.
[0023] Furthermore, the samarium titanate-copper oxide composite active coating is composed of two photocatalytically active substances, samarium titanate and copper oxide. The samarium titanate accounts for 5.6% to 5.9% of the mass of the macroporous hollow water treatment material, and the copper oxide accounts for 3.7% to 4.1% of the mass of the macroporous hollow water treatment material. The relative mass ratio of samarium titanate and copper oxide is an important factor in ensuring the stability and good photocatalytic activity of the material.
[0024] Furthermore, the macroporous hollow water treatment material maintains structural and performance stability below 650°C.
[0025] Furthermore, the diameter of the macroporous hollow water treatment material particles is 0.8–0.9 mm, and the density is 1.2–1.3 g / mL.
[0026] The method for preparing a macroporous hollow water treatment material according to the present invention has the following advantages compared with the prior art:
[0027] This invention uses polyethylene microspheres as an organic template material, coating them with a samarium titanate-copper oxide composite active coating. This material has a density slightly greater than water and exhibits ideal suspension properties under gentle stirring, making it suitable for purifying organic pollutants in wastewater. Furthermore, the material is easily separated from water after the water treatment process, facilitating its recycling. The method provided by this invention allows for the scientific adjustment of the density of the macroporous hollow water treatment material according to the actual conditions of the wastewater, making it applicable to various types of wastewater. The macroporous hollow water treatment material possesses the activity of rapidly degrading organic pollutants in water and has broad application prospects in various organic wastewater treatment fields. Detailed Implementation
[0028] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Operating methods not specifically specified in the following embodiments are generally performed under conventional conditions or as recommended by the manufacturer.
[0029] Unless otherwise specified, all chemical raw materials are pure materials.
[0030] Example 1
[0031] A method for preparing a macroporous hollow water treatment material includes the following process steps:
[0032] Step 1: Preparation of sol precursor
[0033] (1) Add 160 mL of anhydrous ethanol, 7.5 mL of 1,3-butanediol, 5.5 g of samarium nitrate and 8.0 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed;
[0034] (2) Add 2.3g Tween 80, 3.1g copper chloride, and 1.2mL acetic acid to 35mL of pure water and stir until solution B is formed;
[0035] (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor.
[0036] Step 2: Polyethylene microbead gelation and coating
[0037] (1) Add 20g of polyethylene microbeads to the flask containing the sol precursor and continue to reflux at 65℃ for 50min to obtain suspension A;
[0038] (2) The suspension A was concentrated by rotary evaporation at 85°C until the solution volume was reduced by 30% to obtain suspension B.
[0039] Step 3: Solvothermal Synthesis
[0040] (1) The suspension B was transferred into a stainless steel high-pressure reactor. The temperature of the solution in the reactor was controlled at 155°C and the pressure in the reactor was less than 2.2 MPa. The reaction was carried out for 60 h and then cooled to room temperature to obtain suspension C.
[0041] (2) Filter the suspension C and dry the filtered solid at 150°C for 18 hours to obtain solid A.
[0042] Step 4: Heat treatment
[0043] (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours.
[0044] (2) Continue to raise the temperature to 670℃ at a heating rate of 10℃ / min and calcine for 5 hours;
[0045] (3) Cool the above calcined product to room temperature and grind it gently until a loose powder is formed to obtain a macroporous hollow water treatment material with a particle diameter of 0.8-0.9 mm and a density of 1.2 g / mL.
[0046] Example 2
[0047] A method for preparing a macroporous hollow water treatment material includes the following process steps:
[0048] Step 1: Preparation of sol precursor
[0049] (1) Add 165 mL of anhydrous ethanol, 7.8 mL of 1,3-butanediol, 5.7 g of samarium nitrate and 8.3 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed;
[0050] (2) Add 2.4g Tween 80, 3.2g copper chloride, and 1.2mL acetic acid to 37mL of pure water and stir until solution B is formed;
[0051] (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor.
[0052] Step 2: Polyethylene microbead gelation and coating
[0053] (1) Add 20g of polyethylene microbeads to the flask containing the sol precursor and continue to reflux at 65℃ for 50min to obtain suspension A;
[0054] (2) The suspension A was concentrated by rotary evaporation at 85°C until the solution volume was reduced by 30% to obtain suspension B.
[0055] Step 3: Solvothermal Synthesis
[0056] (1) The suspension B was transferred into a stainless steel high-pressure reactor. The temperature of the solution in the reactor was controlled at 158°C and the pressure in the reactor was less than 2.2 MPa. The reaction was carried out for 60 h and then cooled to room temperature to obtain suspension C.
[0057] (2) Filter the suspension C and dry the filtered solid at 150°C for 18 hours to obtain solid A.
[0058] Step 4: Heat treatment
[0059] (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours.
[0060] (2) Continue to raise the temperature to 690℃ at a heating rate of 10℃ / min and calcine for 5 hours;
[0061] (3) Cool the above calcined product to room temperature and grind it gently until a loose powder is formed to obtain a macroporous hollow water treatment material with a particle diameter of 0.8-0.9 mm and a density of 1.2 g / mL.
[0062] Example 3
[0063] A method for preparing a macroporous hollow water treatment material includes the following process steps:
[0064] Step 1: Preparation of sol precursor
[0065] (1) Add 170 mL of anhydrous ethanol, 8.2 mL of 1,3-butanediol, 6.0 g of samarium nitrate and 8.7 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed;
[0066] (2) Add 2.5g Tween 80, 3.4g copper chloride, and 1.2mL acetic acid to 40mL of pure water and stir until solution B is formed;
[0067] (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor.
[0068] Step 2: Polyethylene microbead gelation and coating
[0069] (1) Add 20g of polyethylene microbeads to the flask containing the sol precursor and continue to reflux at 65℃ for 50min to obtain suspension A;
[0070] (2) The suspension A was concentrated by rotary evaporation at 85°C until the solution volume was reduced by 30% to obtain suspension B.
[0071] Step 3: Solvothermal Synthesis
[0072] (1) The suspension B was transferred into a stainless steel high-pressure reactor. The temperature of the solution in the reactor was controlled at 160°C and the pressure in the reactor was less than 2.2 MPa. The reaction was carried out for 60 h and then cooled to room temperature to obtain suspension C.
[0073] (2) Filter the suspension C and dry the filtered solid at 150°C for 18 hours to obtain solid A.
[0074] Step 4: Heat treatment
[0075] (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours.
[0076] (2) Continue to raise the temperature to 710℃ at a heating rate of 10℃ / min and calcine for 5 hours;
[0077] (3) Cool the above calcined product to room temperature and grind it gently until a loose powder is formed to obtain a macroporous hollow water treatment material with a particle diameter of 0.8-0.9 mm and a density of 1.25 g / mL.
[0078] Example 4
[0079] A method for preparing a macroporous hollow water treatment material includes the following process steps:
[0080] Step 1: Preparation of sol precursor
[0081] (1) Add 175 mL of anhydrous ethanol, 8.5 mL of 1,3-butanediol, 6.2 g of samarium nitrate and 9.1 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed;
[0082] (2) Add 2.6g Tween 80, 3.5g copper chloride, and 1.3mL acetic acid to 42mL of pure water and stir until solution B is formed;
[0083] (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor.
[0084] Step 2: Polyethylene microbead gelation and coating
[0085] (1) Add 20g of polyethylene microbeads to the flask containing the sol precursor and continue to reflux at 65℃ for 50min to obtain suspension A;
[0086] (2) The suspension A was concentrated by rotary evaporation at 85°C until the solution volume was reduced by 30% to obtain suspension B.
[0087] Step 3: Solvothermal Synthesis
[0088] (1) The suspension B was transferred into a stainless steel high-pressure reactor. The temperature of the solution in the reactor was controlled at 162°C and the pressure in the reactor was less than 2.2 MPa. The reaction was carried out for 60 h and then cooled to room temperature to obtain suspension C.
[0089] (2) Filter the suspension C and dry the filtered solid at 150°C for 18 hours to obtain solid A.
[0090] Step 4: Heat treatment
[0091] (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours.
[0092] (2) Continue to raise the temperature to 730℃ at a heating rate of 10℃ / min and calcine for 5 hours;
[0093] (3) Cool the above calcined product to room temperature and grind it gently until a loose powder is formed to obtain a macroporous hollow water treatment material with a particle diameter of 0.8-0.9 mm and a density of 1.3 g / mL.
[0094] Example 5
[0095] A method for preparing a macroporous hollow water treatment material includes the following process steps:
[0096] Step 1: Preparation of sol precursor
[0097] (1) Add 180 mL of anhydrous ethanol, 9 mL of 1,3-butanediol, 6.5 g of samarium nitrate and 9.5 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed;
[0098] (2) Add 2.7g Tween 80, 3.6g copper chloride, and 1.3mL acetic acid to 45mL of pure water and stir until solution B is formed;
[0099] (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor.
[0100] Step 2: Polyethylene microbead gelation and coating
[0101] (1) Add 20g of polyethylene microbeads to the flask containing the sol precursor and continue to reflux at 65℃ for 50min to obtain suspension A;
[0102] (2) The suspension A was concentrated by rotary evaporation at 85°C until the solution volume was reduced by 30% to obtain suspension B.
[0103] Step 3: Solvothermal Synthesis
[0104] (1) The suspension B was transferred into a stainless steel high-pressure reactor. The temperature of the solution in the reactor was controlled at 165°C and the pressure in the reactor was less than 2.2 MPa. The reaction was carried out for 60 h and then cooled to room temperature to obtain suspension C.
[0105] (2) Filter the suspension C and dry the filtered solid at 150°C for 18 hours to obtain solid A.
[0106] Step 4: Heat treatment
[0107] (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours.
[0108] (2) Continue to raise the temperature to 750℃ at a heating rate of 10℃ / min and calcine for 5 hours;
[0109] (3) Cool the above calcined product to room temperature and grind it gently until a loose powder is formed to obtain a macroporous hollow water treatment material with a particle diameter of 0.8-0.9 mm and a density of 1.3 g / mL.
Claims
1. A method for preparing a macroporous hollow water treatment material, characterized in that, The process includes the following steps: Step 1: Preparation of sol precursor (1) Add 160-180 mL of anhydrous ethanol, 7.5-9 mL of 1,3-butanediol, 5.5-6.5 g of samarium nitrate, and 8.0-9.5 mL of tetrabutyl titanate to a flask in sequence, and stir until solution A is formed; (2) Add 2.3-2.7g Tween 80, 3.1-3.6g copper chloride, and 1.2-1.3mL acetic acid to 35-45mL of pure water, and stir until solution B is formed; (3) Slowly add solution B to solution A, heat to 65°C, and reflux for 75 min to obtain the sol precursor; Step 2: Polyethylene microbead gelation and coating (1) Add 20g of polyethylene microspheres to a flask containing the sol precursor, and continue reflux at 65℃ for 50min to obtain suspension A; the polyethylene microspheres have a particle diameter of 0.7~0.8mm and a density of 1.0g / mL. (2) Concentrate suspension A by rotary evaporation at 85°C until the volume of suspension A is reduced by 30% to obtain suspension B; Step 3: Solvothermal Synthesis (1) Transfer suspension B into a stainless steel high-pressure reactor, control the solution temperature in the reactor to 155~165℃, the pressure in the reactor to less than 2.2MPa, react for 60h, and then cool to room temperature to obtain suspension C; (2) Filter the suspension C, and dry the solid obtained by filtration at 150°C for 18 hours to obtain solid A; Step 4: Heat treatment (1) Place the solid A obtained in step 3 into a programmable box furnace and raise the temperature to 360°C at a heating rate of 5°C / min, and keep it at that temperature for 3 hours. (2) Continue to raise the temperature to 670~750℃ at a heating rate of 10℃ / min, calcine for 5h, and obtain the calcined product; (3) Cool the calcined product to room temperature and grind it into a loose powder to obtain a macroporous hollow water treatment material; the macroporous hollow water treatment material has a particle diameter of 0.8~0.9mm and a density of 1.2~1.3g / mL; The macroporous hollow water treatment material has a samarium titanate-copper oxide composite active coating coated on polyethylene microspheres. The coating is firmly bonded to the polyethylene microspheres. The samarium titanate accounts for 5.6% to 5.9% of the mass of the macroporous hollow water treatment material, and the copper oxide accounts for 3.7% to 4.1% of the mass of the macroporous hollow water treatment material.
2. A macroporous hollow water treatment material, prepared by the method of claim 1, characterized in that, The samarium titanate-copper oxide composite active coating is composed of two photocatalytically active substances: samarium titanate and copper oxide.
3. The macroporous hollow water treatment material according to claim 2, characterized in that, The macroporous hollow water treatment material maintains structural and performance stability below 650°C.
Citation Information
Patent Citations
Preparation method of macroporous hollow cerium titanate microspheres
CN107082447A
Cerium oxide material as well as preparation method and application thereof
CN112919522A
